2022
DOI: 10.3389/fnmol.2022.800406
|View full text |Cite|
|
Sign up to set email alerts
|

Menthol Flavor in E-Cigarette Vapor Modulates Social Behavior Correlated With Central and Peripheral Changes of Immunometabolic Signalings

Abstract: The use of electronic cigarette (e-cigarette) has been increasing dramatically worldwide. More than 8,000 flavors of e-cigarettes are currently marketed and menthol is one of the most popular flavor additives in the electronic nicotine delivery systems (ENDS). There is a controversy over the roles of e-cigarettes in social behavior, and little is known about the potential impacts of flavorings in the ENDS. In our study, we aimed to investigate the effects of menthol flavor in ENDS on the social behavior of lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 77 publications
0
7
0
3
Order By: Relevance
“…Time around and the number of interactions with each cup, and the time spent in each chamber was recorded. Calculations of preference of index and preference of chambers were described in previous studies[22].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time around and the number of interactions with each cup, and the time spent in each chamber was recorded. Calculations of preference of index and preference of chambers were described in previous studies[22].…”
Section: Methodsmentioning
confidence: 99%
“…Many evidence has been obtained from cell cultures [46], animal models [79] and human subjects [1013] to compare the vaping with smoking and assesses the impact of e-cigarettes on human health, especially the lung functions as well as cancer, oxidative stress, and inflammation related molecular signals [1419]. A few studies on the cognitive and affective alterations after long-term exposure to tobacco smoke or e-cigarette vapour have demonstrated that, e-cigarette nicotine vapor exposure increased levels of locomotor activity during late prenatal and early postnatal life [20]; It has been recently reported that nicotine vapor exposure impairs the risk-based decision making in adult rats [21]; our previous work indicated that menthol flavor in e-cigarette vapor increases social behaviors in mice [22]. The potential mechanisms may include nicotine-related alterations of neurotransmitters and chemicals that signal inflammation in certain brain regions, such as the decreased dopamine concentration in the striatum and GABA in the frontal cortex, while increased levels of glutamate in the striatum and glutamine in the frontal cortex and striatum by chronic inhalation of e-cigarette vapor containing nicotine [23]; the reduced gene expression of Ngfr and Bdnf , and increased expression of IBA-1, a specific marker of microglia in the hippocampus [24]; changes on the CNS development-related gene profile in the frontal cortex [25]; and cytokines such as interleukin IL-4 and interferon-gamma (IFN-γ) in the diencephalon, as well as levels of hippocampal IFN-γ, and IL-6 in the cerebellum in the offspring of mice exposed prenatally to e-cigarette aerosols [26].…”
Section: Introductionmentioning
confidence: 99%
“…Der einzige Geschmackszusatz, der in Mäusen ein aversives Verhalten auslöste, war Tabakgeschmack [24]. Über eine abhängigkeitsfördernde Wirkung hinaus wurde gezeigt, dass Mentholzusatz in nikotinhaltigem Dampf die soziale Aktivität erhöht und zu Veränderungen des Metabolismus im Hippocampus und des peripheren Immunsystems führt [25]. Einige Untersuchungen adressieren spezifische Effekte von Aromen bei jungen Säugetieren.…”
Section: Generelle Toxikologische Betrachtungen Zu E-zigarettenunclassified
“…Ein physiologisches Korrelat dafür fand eine funktionelle MRT-Studie: Werbung für E-Zigaretten mit fruchtigen und süßen Aromen induzierte bei jungen E-Zigaretten-Nutzenden, die sonst Nichtrauchende waren, im Gegensatz zu Tabakaromen eine erhöhte Aktivität im Nucleus accumbens [34]. Bestimmte Aromen wie Erdbeere führten im Vergleich zu vorher genutzten Aromen oder Tabakgeschmack zu einem verlängerten Zugverhalten und damit bei gleichen Nikotinkonzentrationen des Liquids zu einem höheren Nikotinspiegel [25,26].…”
Section: Humane Datenunclassified
“…17 Following long-term exposure to the menthol flavor of an electronic nicotine delivery system, serum cytokines decreased peripheral immunometabolic responses in mice. 18…”
Section: Introductionmentioning
confidence: 99%